2021
DOI: 10.25026/jsk.v3i2.483
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Obesitas dengan Komplikasi Maternal dan Luaran Perinatal

Abstract: Obesity is a global health problem which numbers continue to increase from year to year. Obesity is a risk factor for maternal complications and adverse perinatal outcomes. This systematic review aims to evaluate the association of obesity with maternal complications and perinatal outcomes. This systematic review was conducted by searching for studies on databases such as Pubmed, Google Scholar, Science Direct or Clinical Key and the studies observed are studies published in 2016-2020 in Indonesian and English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…When looking at the number of pregnant women who are thought to be at the highest risk, they are in the category of pregnant women who have the BMI/BMI category of excess weight and obesity, namely four people (8%). Based on a systematic review conducted Mulyani et al 4 , obesity in women before pregnancy was noted to have a relationship with the occurrence of gestational diabetes in 96% of studies from a total of 25 studies that were observed in as many as 16 studies showed that obesity was significantly associated with the incidence of gestational diabetes. with p <0.05 (n=7) and p<0.001 (n=9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When looking at the number of pregnant women who are thought to be at the highest risk, they are in the category of pregnant women who have the BMI/BMI category of excess weight and obesity, namely four people (8%). Based on a systematic review conducted Mulyani et al 4 , obesity in women before pregnancy was noted to have a relationship with the occurrence of gestational diabetes in 96% of studies from a total of 25 studies that were observed in as many as 16 studies showed that obesity was significantly associated with the incidence of gestational diabetes. with p <0.05 (n=7) and p<0.001 (n=9).…”
Section: Discussionmentioning
confidence: 99%
“…Women with excess nutritional status or obesity have a higher risk for gestational diabetes, cesarean section, uterine rupture, postpartum hemorrhage, fetal macrosomia, fetal death, spontaneous abortion, meconium aspiration, fetal distress, and congenital abnormalities 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Sedangkan risiko lain pada janin adalah makrosomia, IUGR, kelahiran prematur, bahkan dapat meningkatkan angka kejadian kematian perinatal. 5,9 Masalah obesitas dalam kehamilan memiliki hubungan dengan kejadian anemia. Orang dengan obesitas memiliki kecederungan memilih jenis makanan yang tidak sehat seperti makanan yang tinggi lemak, tinggi gula, dan kurang serat.…”
Section: Pendahuluanunclassified
“…Studi prospektif yang dilakukan di Pakistan dan India menemukan bahwa kelahiran prematur lebih berpeluang terjadi pada ibu dengan hipertensi dalam kehamilan, pre-eklampsia dan eklampsia yang lebih sering terjadi pada wanita overweight dan obesitas. (Mulyani et al, 2021).…”
Section: Hasil Dan Pembahasanunclassified